Analisis Penilaian Afektif Pembelajaran Daring Menggunakan Learning Management System (LMS) pada Mata Pelajaran Matematika - Muhassanah, Nur'aini; Kartika, Dwiani Listya (Institut Agama Islam Negeri Curup, 2021)
The purpose of this study was to describe affective assessment in mathematics subjects using LMS media as a media to support learning activities between students and teachers in online learning. The subjects of this study were 214 students who were divided into five classes in class XI IPA SMA Negeri 1 Purbalingga. This research was conducted in July – September 2021. The data in this study were obtained from the results of filling out questionnaires related to affective assessment in online learning. The scale used to measure the affective aspect of the activities of an object is the Likert scale. The data analysis technique used descriptive statistical methods. The results showed that the implementation of the affective domain assessment in online learning through the Learning Management System (LMS) in the mathematics subjects of class XI science students at SMA Negeri 1 Purbalingga was running well. Teachers and students can already use the application as expected so that students can follow the learning well. With the LMS, it is easier for students to understand the material, get assignments and assessments and can interact and discuss with the teacher smoothly. In addition, students also remain highly motivated even though learning cannot be done face-to-face.